Rhenium-promoted selective CO2 methanation on Ni-based catalyst. (July 2018) - Yuan, Hongjuan; Zhu, Xinli; Han, Jinyu; Wang, Hua; Ge, Qingfeng
Graphical abstract: Highlights: The Re@Ni(111) surface improves the adsorption of oxygen-containing intermediates due to the strong affinity of Re to O. The presence of Re significantly lowers the activation barrier of CO bond cleavage. Microkinetic analysis showed that the presence of Re greatly increases the selectivity toward CH4 . Abstract: Re-doped Ni(111) (Re@Ni(111)) surface was used as a model to investigate the effect of Re on the CO bond scission and on the selectivity of CO2 methanation on a Ni-based catalyst. Three pathways, including CO2 dissociation into CO* followed by CO* hydrogenation, CO2 reduction through the HCOO* and COOH* intermediates, were analyzed based on the results from the density functional theory calculations. The results indicate that the presence of Re significantly lowers the activation barrier of CO bond cleavage due to the strong affinity of Re to O but has no significant effect on the hydrogenation steps. Microkinetic analysis showed that the presence of Re greatly increases the selectivity toward CH4 . Analysis of surface coverage of the adsorbed species showed that CO* and H* were the most abundant species on the Ni(111) surface whereas appreciable amount of O adatoms were present on Re@Ni(111) in addition to CO* and H*, with the O adatoms on the Re sites. On both surfaces, increasing H2 partial pressure resulted in an increase in H* coverage but decreased CO* coverage. The strong affinity of Re toward O makes Re@Ni(111) more effective for CO bond scission and thereby enhances methane selectivity.